An Overview of Financial Stress and Health Outcomes: The Moderating Role of Social Support - Fatin Athirah Mohd Fazi; Siti Nurul Akma Ahmad; Nurul Amyra Mat Isa; Siti Mariam Ali (Information Management and Business Review, 2025)
Investigating the population's health and well-being has been a topic of interest in recent years due to the remarkable growth.  The Sustainable Development Goals (SDG) index indicates that Malaysian health and wellbeing issues remain significant challenges.  Taking into account the important aspects, a PwC Asia Pacific survey from 2023 revealed that individuals’ financial circumstances have been the primary cause of stress, which affects both their mental and physical health.  This is also confirmed by the Bank Negara Malaysia (BNM) which reported that household members are currently experiencing financial stress with B40 income groups being particularly vulnerable to issues related to the increase in cost of living and loss of income. Therefore, the purpose of this study is to discuss the influence of financial stress on health-related outcomes and social support as the role that buffers the relationship. The role of social support, as suggested by previous research, as an element in reducing stress, may improve the emotional stability, mental and physical health of individuals. The present study offers valuable insights for employers and organizations to provide focused interventions in strengthening social support to improve employees’ health and well-being.